Problems of the Investigation and Prosecution in case of Piracy at Sea - Kiš, Amarila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Sea piracy became a current topic around 2008 when the number of attacks increased in the Gulf of Aden. However it is more or less repressed by now, piracy has a unique shifting nature: it decreases in one region, but it increases in another, therefore it is always present to some extent. Besides, Somali piracy was the first that made international community to take steps and these strategies and programmes serve as an important lesson that can be partly adaptable in other cases as well. It reveals important questions around enforcement jurisdiction and the most exciting problem: prosecutions. This paper attempts to briefly take a glance at those difficulties that can set back the success of a piracy prosecution and if there is a progress. First, it presents the root-cause: jurisdiction. National laws regulate piracy in a very different way or they don’t criminalize them at all and this can lead serious consequences. In the following chapter the process of investigation is presented. Collecting evidence is incredibly difficult in case of piracy and if it fails, prosecutions fail tool. In the end the paper attempts to focus on the trial and what follows: costs of prosecutions, asylum-seekers, human rights considerations and prison facilities.